HIV-exposed uninfected infants show robust memory B cell responses in spite of a delayed accumulation of memory B cells: an observational study in the first two years of life - Nduati, E; Nkumama, I; Gambo, F; Muema, D; Garcia-Knight, M; Hassan, A; Jahangir, M; Etyang, T; Berkley, J; Urban, B (American Society for Microbiology, 2016)
Background Improved HIV care has led to an increase in the number of HIV-exposed uninfected (HEU) infants born to HIV infected women. Although uninfected, these infants experience increased morbidity and mortality. One explanation may be that their developing immune system is altered by HIV-exposure predisposing them to increased post-natal infections. Methods We explored the impact of HIV-exposure on the B-cell compartment by determining the B-cell subset distribution, the frequency of common vaccine antigen-specific memory B cells (MBCs) and their respective antibody levels in HEU and HIV-unexposed uninfected (HUU) infants born to uninfected mothers, using flow cytometry, B-cell ELISPOT and ELISA, respectively, during the first two years of life. Results For the majority of the B-cell subsets there were no differences between HEU and HUU infants. However, HIV exposure was associated with a lower proportion of B cells in general and specifically MBCs, largely due to a lower proportion of unswitched memory B cells. This reduction was maintained even after correcting for age. These phenotypic differences in the MBC compartment did not affect the ability of HEU infants to generate recall responses to previously encountered antigens, or reduce the antigen-specific antibody levels at 18 months of life. Conclusions Although HIV-exposure was associated with a transient reduction in the proportion of MBCs, we found that the ability of HEUs to mount robust MBC and serological responses was unaffected.